2011
DOI: 10.1063/1.3627152
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Configuration interaction singles has a large systematic bias against charge-transfer states

Abstract: We show that standard configuration interaction singles (CIS) has a systematic bias against chargetransfer (CT) states, wherein the computed vertical excitation energies for CT states are disproportionately too high (by >1 eV) as compared with non-CT states. We demonstrate this bias empirically for a set of chemical problems with both inter-and intra-molecular electron transfer, and then, for a small analytical model, we prove that this large difference in accuracy stems from the massive changes in electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 34 publications
6
107
0
Order By: Relevance
“…4 For all of the reasons above, over the last year, our research group has attempted to use CIS theory to consider electron transfer events between excited states, though we have had little success. As we showed in a recent publication, 5 even though CIS recovers the correct −1/r asymptotic behavior of a) Electronic mail: subotnik@sas.upenn.edu.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…4 For all of the reasons above, over the last year, our research group has attempted to use CIS theory to consider electron transfer events between excited states, though we have had little success. As we showed in a recent publication, 5 even though CIS recovers the correct −1/r asymptotic behavior of a) Electronic mail: subotnik@sas.upenn.edu.…”
Section: Introductionsupporting
confidence: 60%
“…In Ref. 5, we showed that CIS(D) gives a strong correction, lowering the energy of the CT state (making it the first or second excited state), and that correction is to a good approximation proportional to the excited state relative dipole moment. If OO-CIS is a valid theory, we expect that it should behave similarly.…”
Section: Results: 2-(4-(propan-2-ylidene) Cyclohexylidene)malonomentioning
confidence: 99%
“…In particular, CIS fails miserably when it comes to the relative energies of non-CT and CT states, consistently overestimating CT energies by roughly 1-2 eV. 2 To improve upon CIS with wavefunctions, CIS(D) 3 is a good approach, introducing electron correlation by including perturbations from all doubles and a subset of the triples. (Another option is CIS(2).…”
Section: Cis Inspired Approaches Configuration Interaction Singles (mentioning
confidence: 99%
“…Previously, 2 we have generated 500 geometries from a ground-state classical trajectory, and we consider the first 12 excited states, each with roughly 1 CT state apiece, for a total of 6000 data points. In this region of configuration space, with no torsional motion, we do not expect to see any crossings between the CT and non-CT state.…”
Section: Pycmmentioning
confidence: 99%
“…15 The double excitations problem seems still open. 16 The simplest wavefunction method for excited states, configuration interaction singles (CIS), overestimates the energy of CT states 17 and does not describe double excitations. In equation-of-motion coupled cluster (EOM-CC) theory 18 including its local variants, 19,20 triple displacements (the so-called EOM-CCSDT or CC3 models) are needed to quantitatively describe excited states with strong double excitation character, which are nonetheless expensive.…”
mentioning
confidence: 99%